100 essential triathlon sessions the definitive training programme for all serious triathletes - Trew, Steve (The Crowood Press, 2014)
This title includes the definitive training programme for all serious triathletes. These 100 sessions - 30 swim, 30 bike, 30 run and 10 brick - have been developed and honed over many years and have proved effective in improving performance: The Brick sessions ; Progression in training